Adenocarcinoma Ex Goblet Cell Carcinoid of Appendix: Two Case Reports. (14th August 2017) - Wang, Yu-Ting; Li, Yi-Ru; Ke, Tuan-Ying
Abstract : Adenocarcinoma ex goblet cell carcinoid is a rare tumor incidentally found in specimens of appendicitis. Most patients present with acute abdomen, similar to acute appendicitis. Here we present two cases, which were found incidentally after operation. We give a brief summary about clinical and biological behavior of this entity.